Flame-retardant polyester resin composition and molded article made thereof

JP7643339B2Active Publication Date: 2025-03-11TOYOBO MC CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021554974
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-19
Filing Date
2021-02-15
Publication Date
2025-03-11
Estimated Expiration
2041-02-15

AI Technical Summary

Benefits of technology

【0010】 本発明の難燃性ポリエステル樹脂組成物は、耐熱性に優れ、ソリ変形が少なく成形品外観が良好で、かつ高強度·高剛性と難燃性を両立した成形品を得ることができ、さらに、優れた滞留安定性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643339000006
    Figure 0007643339000006
  • Figure 0007643339000001
    Figure 0007643339000001
  • Figure 0007643339000002
    Figure 0007643339000002
Patent Text Reader

Abstract

The present invention is a flame retardant polyester resin composition which exhibits excellent residence stability and which can yield a molded article that has excellent heat resistance, little warping, and good molded article appearance and that achieves a balance between high strength / rigidity and flame retardancy. The flame retardant polyester resin composition contains 3-74 mass% of a poly(butylene phthalate) resin (A), 3-60 mass% of a poly(ethylene terephthalate) resin (B1), 3-50 mass% of a copolyester resin (B2), 10-50 mass% of a halogen-free flame retardant (C) and 10-40 mass% of glass fibers (D). The copolyester resin (B2) is a polyester resin which is obtained by copolymerizing ethylene terephthalate units with at least one type selected from the group consisting of neopentyl glycol, 1,2-propane diol, diethylene glycol, 1,4-cyclohexanedimethanol and isophthalic acid and which satisfies prescribed characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass fiber reinforced polyester resin composition that has been flame retarded with a halogen-free flame retardant. More specifically, the present invention relates to a flame retardant polyester resin composition that can provide halogen-free flame retardant molded products that have high rigidity and strength, but also have little glass fiber lifting, excellent molded product appearance, and little warpage. [Background technology]

[0002] Polyester resins have excellent mechanical properties, heat resistance, and chemical resistance, and therefore flame-retardant polyester resin compositions prepared by blending polyester resins with flame retardants have been widely used in various parts that require flame retardancy, such as automobile parts, electric and electronic parts, and industrial machine parts.

[0003] In particular, housings for electronic devices and the like are required to have not only flame retardancy, but also rigidity, good appearance, and excellent low warpage.

[0004] For making polyester resin flame retardant, so-called halogen-based flame retardants, which are a mixture of bromine-based flame retardants and antimony compounds, have been generally used, but they have problems such as a large amount of smoke generated during combustion and the possibility of emitting harmful substances during combustion. In recent years, therefore, polyester resin compositions flame retarded by flame retardants that do not contain any of these halogens have been demanded, and various flame retardant methods using nitrogen-containing compounds and phosphorus-based compounds have been proposed. For example, Patent Document 1 discloses a flame retardant resin composition composed of polyalkylene terephthalate, a reinforcing filler, a melamine-cyanuric acid adduct, and a resorcinol bisaryl phosphate. Patent Document 2 discloses a flame retardant polyester composition composed of a reinforcing component and a polymer component containing a mixed flame retardant containing poly(butylene terephthalate), an aromatic phosphate oligomer, and melamine pyrophosphate. Patent Document 3 discloses a flame retardant resin composition containing a thermoplastic resin, a phosphorus compound having a phosphonyl group (>P(=O)H), and a phenolic resin. Furthermore, a flame-retardant resin composition is disclosed that uses a flame retardant combination containing an organic phosphinate salt and a reaction product of melamine and phosphoric acid or a reaction product of a melamine condensate and phosphoric acid (Patent Document 4). However, these documents do not include information on how to precisely control the balance between flame retardancy, warpage, mechanical property retention, moldability, and appearance properties.

[0005] On the other hand, it has been disclosed that in order to obtain a polyester resin molded article that has little warpage and that combines high strength, high rigidity, and good molded article appearance, it is effective to control the solidification speed of the polyester resin composition in the molding die (Patent Document 5). However, there is no mention of a composition containing less than 30 mass% of inorganic reinforcing material, and further, the addition of a flame retardant required to achieve V-0 flame retardancy tends to cause decomposition of the polyester and a decrease in mechanical properties, but Patent Document 5 does not disclose any means for achieving both flame retardancy and high rigidity. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 5-70671 [Patent Document 2] Japanese Patent Application Publication No. 11-152402 [Patent Document 3] JP 2000-103973 A [Patent Document 4] JP 2001-72978 A [Patent Document 5] Patent No. 5396690 Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made to solve such problems, and an object of the present invention is to provide a flame-retardant polyester resin composition that can give molded articles that have excellent heat resistance, little warpage, good appearance, and high strength, high rigidity, and flame retardancy. In addition, it has been newly discovered that the type of flame retardant affects the retention stability of a flame-retardant polyester resin composition, and it is an object of the present invention to provide a flame-retardant polyester resin composition that has excellent retention stability in addition to the above properties. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems and found that the above-mentioned balance of properties can be maintained to a high degree by incorporating polybutylene phthalate resin, polyethylene terephthalate resin, copolymer polyester resin, flame retardant, and glass fiber in a predetermined compounding ratio.

[0009] That is, the present invention is as follows. [1] A flame-retardant polyester resin composition comprising: 3 to 74 mass% of a polybutylene phthalate resin (A), 3 to 60 mass% of a polyethylene terephthalate resin (B1), 3 to 50 mass% of a copolymer polyester resin (B2), 10 to 50 mass% of a halogen-free flame retardant (C), and 10 to 40 mass% of glass fiber (D), the copolymerized polyester resin (B2) is a polyester resin in which ethylene terephthalate units are copolymerized with at least one member selected from the group consisting of neopentyl glycol, 1,2-propanediol, diethylene glycol, 1,4-cyclohexanedimethanol, and isophthalic acid, The flame-retardant polyester resin composition has a melt mass-flow rate (MFR) of 10 g / 10 min or more at a moisture content of 0.05% or less (measured at 265° C. and a load of 2160 g in accordance with JIS K 7210-1:2014); The flame-retardant polyester resin composition exhibits flame retardancy of UL94 standard V-0 (1 / 16 inch thickness), The flame-retardant polyester resin composition has a flexural strength of 140 MPa or more as measured in accordance with ISO-178, and satisfies the following formula (1): 0.5≦β / α (1) (Here, α is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265°C and a residence time of 5 minutes, and β is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265°C and a residence time of 10 minutes.) [2] The flame-retardant polyester resin composition according to [1], wherein the halogen-free flame retardant (C) contains a metal phosphinate. [3] A molded article, which is an electric / electronic part, an office automation device, a home appliance part, an automobile part, or a machine mechanism part, comprising the flame-retardant polyester resin composition according to [1] or [2]. Effect of the Invention

[0010] The flame-retardant polyester resin composition of the present invention has excellent heat resistance, is less prone to warpage, and produces molded articles with good appearance, and is capable of yielding molded articles that combine high strength, high rigidity, and flame retardancy, and further has excellent retention stability. [Brief description of the drawings]

[0011] [Figure 1]FIG. 1A is a schematic top view and FIG. 1B is a schematic side view showing an example of a molded product molded for evaluating warpage deformation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be specifically described below. The content (blending amount) of each component in the flame-retardant polyester resin composition of the present invention is the amount when the flame-retardant polyester resin composition is 100 mass %. The blending amount of each component during the production of the flame-retardant polyester resin composition is the content in the flame-retardant polyester resin composition.

[0013] The polybutylene terephthalate resin (A) in the present invention is a thermoplastic polyester resin obtained by polycondensation of terephthalic acid and 1,4-butanediol, and has a reduced viscosity (a 0.1 g sample is dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30°C using an Ubbelohde viscosity tube: unit dL / g) preferably in the range of 0.4 to 1.2 dL / g, more preferably in the range of 0.5 to 0.9 dL / g. If the reduced viscosity is less than 0.4 dL / g, the toughness decreases, and if it exceeds 1.2 dL / g, the fluidity decreases, and the desired good appearance of the molded product may not be obtained.

[0014] The amount of polybutylene terephthalate resin (A) in the flame-retardant polyester resin composition of the present invention is 3 to 74 mass%, preferably 10 to 70 mass%, more preferably 20 to 60 mass%, even more preferably 30 to 55 mass%, particularly preferably 30 to 45 mass%, and most preferably 32 to 42 mass%.

[0015] The polyethylene terephthalate resin (B1) in the present invention is a thermoplastic polyester resin obtained by polycondensation of terephthalic acid and ethylene glycol, and has a reduced viscosity (a 0.1 g sample is dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30°C using an Ubbelohde viscosity tube: unit dL / g) preferably in the range of 0.4 to 1.0 dL / g, more preferably in the range of 0.5 to 0.9 dL / g. If the reduced viscosity is less than 0.4 dL / g, the toughness decreases, and if it exceeds 1.0 dL / g, the fluidity decreases, and the desired good appearance of the molded product may not be obtained.

[0016] The content of the polyethylene terephthalate resin (B1) in the flame-retardant polyester resin composition of the present invention is 3 to 60 mass%, preferably 3 to 50 mass%, more preferably 3 to 45 mass%, even more preferably 3 to 25 mass%, particularly preferably 4 to 15 mass%, and most preferably 4 to 12 mass%.

[0017] The copolymerized polyester resin (B2) in the present invention is a polyester resin obtained by copolymerizing at least one copolymerization monomer selected from the group consisting of neopentyl glycol (NPG), 1,2-propanediol (1,2PG), diethylene glycol (DEG), 1,4-cyclohexanedimethanol (CHDM), and isophthalic acid (IPA) with ethylene terephthalate units consisting of terephthalic acid (TPA) and ethylene glycol (EG). The copolymerization amount of these copolymerization monomers is preferably 20 to 70 mol %, more preferably 20 to 60 mol %, and even more preferably 25 to 50 mol % for at least one component, when the acid component constituting the copolymerized polyester resin (B2) is 100 mol % and the glycol component is 100 mol %.

[0018] In the copolymer polyester resin (B2), in addition to the above-mentioned copolymerizable monomers, acid components such as sebacic acid (SA), adipic acid (AA), 2,6-naphthalenedicarboxylic acid (NPA), trimellitic acid (TMA), etc., and glycol components such as 1,4-butanediol (BD), 1,3-propanediol (1,3PG), 2-methyl-1,3-propanediol (2MG), polytetramethylene glycol (PTMG), ε-caprolactone, polycarbonate diol, etc. may be copolymerized.

[0019] Specific examples of copolymer polyester resins include, but are not limited to, TPA / / EG / NPG copolymer, TPA / IPA / / EG copolymer, TPA / / EG / 1,2PG copolymer, TPA / IPA / / EG / NPG copolymer, TPA / / EG / CHDM copolymer, TPA / IPA / TMA / / 2MG / 1,2PG copolymer, TPE / IPA / TMA / / 2MG / CHDM copolymer, TPA / IPA / SA / / EG / NPG / CHDM copolymer, and TPA / IPA / / EG / 1,3PG copolymer.

[0020] The reduced viscosity (a 0.1 g sample is dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4) and measured at 30°C using an Ubbelohde viscosity tube: unit dL / g) of the copolymer polyester resin (B2) used in the present invention varies slightly depending on the specific copolymer polyester resin, but is preferably 0.4 to 1.5 dL / g, more preferably 0.4 to 1.3 dL / g. If the reduced viscosity is less than 0.4 dL / g, toughness decreases, while if it exceeds 1.5 dL / g, fluidity decreases.

[0021] The blending amount of the copolymer polyester resin (B2) in the present invention is 3 to 50 mass%, preferably 3 to 40 mass%, more preferably 3 to 30 mass%, further preferably 3 to 20 mass%, and particularly preferably 4 to 15 mass%. If the blending amount exceeds 50 mass%, the heat resistance (deflection temperature under load (HDT)) decreases.

[0022] The halogen-free flame retardant (C) in the present invention may be, for example, a phosphorus-based flame retardant or a non-phosphorus-based flame retardant. Phosphorus-based flame retardants include red phosphorus compounds, metal phosphinates (c1), reaction products of melamine and phosphoric acid (c2), phosphazene compounds (c3) and phosphinic acid derivatives (c4), which can be used alone or in combination.

[0023] The metal phosphinate (c1) is at least one of a phosphinate represented by the following general formula (1) and a diphosphinate represented by the following general formula (2).

[0024] [ka]

[0025] [ka]

[0026] [In general formulas (1) and (2), R 1 and R 2 are the same or different, linear or branched alkyl and / or aryl having 1 to 6 carbon atoms, R 3 is a linear or branched alkylene having 1 to 10 carbon atoms, an arylene having 6 to 10 carbon atoms, an alkylarylene having 6 to 10 carbon atoms, or an arylalkylene having 6 to 10 carbon atoms; M is any one of a calcium ion, a magnesium ion, an aluminum ion, and a zinc ion; m is 2 or 3; n is 1, 2, or 3; and x is 1 or 2.

[0027] R 1 and R 2 is preferably methyl, ethyl, or n-propyl, isopropyl, n-butyl, tert-butyl, n-pentene and / or phenyl.

[0028] R 3is preferably methylene, ethylene, n-propylene, isopropylene, n-butylene, tert-butylene, n-pentylene, n-octene, n-propylene, phenylene, naphthylene, methylphenylene, ethylphenylene, tert-butylphenylene, methylnaphthylene, ethylnaphthylene, or tert-butylnaphthylene, phenylmethylene, phenylethylene, phenylpropylene, or phenylbutylene.

[0029] M is preferably an aluminum ion, a zinc ion or a calcium ion.

[0030] The term "phosphinates" as used below encompasses phosphinates and diphosphinates and their polymers, which are prepared in aqueous media and are essentially monomeric compounds, although depending on the reaction conditions, polymeric phosphinates may also form under certain circumstances.

[0031] Phosphinic acids suitable as a component of the phosphinic salts are, for example, dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylenephosphinic acid, methane-1,2-di(methylphosphinic acid), benzene-1,4-(dimethylphosphinic acid), methylphenylphosphinic acid and diphenylphosphinic acid.

[0032] The phosphinate salt in the present invention can be prepared by a known method such as that described in EP-A-699708. For example, the phosphinate salt can be prepared by reacting the phosphinate salt with a metal carbonate, metal hydroxide, or metal oxide in an aqueous solution. The phosphinate salt used in the present invention can be a known compound, among which aluminum phosphinate is preferred.

[0033] The reaction product (c2) of melamine and phosphoric acid in the present invention is a cyanamide derivative having at least one amino group or a reaction product of the cyanamide derivative and phosphoric acid, specifically, an amino group and -N=C=N- or -N=C(-N<) 2 The cyanamide derivatives include cyclic cyanamide derivatives such as amino group-containing triazines (amino group-containing 1,3,5-triazines such as melamine, melam, melem, melon, guanamine, acetoguanamine, and benzoguanamine, and amino group-containing 1,2,4-triazines such as 3-amino-1,2,4-triazine), amino group-containing triazoles (amino group-containing 1,3,4-triazoles such as 2,5-diamino-1,3,4-triazole), and non-cyclic cyanamide derivatives such as guanidines (guanidine, guanidine derivatives (dicyandiamide, guanidyl urea, etc.)). Preferred cyanamide derivatives are amino group-containing 1,3,5-triazines, guanidine, or derivatives thereof, particularly melamine. In the case of melamine, melamine cyanurate can also be used as one of the derivatives. Such cyanamide derivatives can be used alone or in combination of two or more.

[0034] In the present invention, the cyanamide derivative having at least one amino group or the reaction product of the cyanamide derivative and phosphoric acid is preferably at least one of a melamine condensation product, a reaction product of melamine or a melamine condensation product and phosphoric acid, and a reaction product of a melamine and a phosphoric acid condensate, more preferably melamine polyphosphate, melem polyphosphate, melam polyphosphate, dimelamine pyrophosphate, and particularly preferably melamine polyphosphate (melamine polyphosphate) having a condensation degree of 2 or more, particularly a long chain length of 10 or more and 50 or less.

[0035] The phosphazene compound (c3) in the present invention is an organic compound having a -P=N- bond in the molecule, preferably a cyclic phenoxyphosphazene or a chain phenoxyphosphazene having a structure represented by the following general formula (3) in the molecule, or a crosslinked phenoxyphosphazene compound in which at least one type of phenoxyphosphazene is crosslinked by a crosslinking group. Specifically, examples of the cyclic phosphazene include cyclic phenoxyphosphazene such as SPE-100 (trade name) manufactured by Otsuka Chemical Co., Ltd., cyclic cyanophenoxyphosphazene such as FP-300 (trade name) manufactured by Fushimi Pharmaceutical Co., Ltd., and SPH-100 (trade name) manufactured by Otsuka Chemical Co., Ltd. Since chain phenoxyphosphazene, crosslinked phenoxyphosphazene, etc. have a substituent at the molecular end, the phosphorus content is generally lower than that of cyclic phosphazene, but bleeding, etc., tends to be suppressed, and it is necessary to use them according to the type of resin to be added.

[0036] [ka]

[0037] (In general formula (3), X is a phenoxy group, and n is an integer of 3 to 10,000.)

[0038] Moreover, since non-reactive phosphazenes may bleed onto the surface over time, may be affected by hydrolysis under harsh conditions of use to elute free phosphorus, or may have degraded insulating properties due to decomposition products, it is more preferable to select reactive phosphazenes having functional groups that have affinity with polyamides, such as cyclic hydroxyphenoxyphosphazenes having hydroxyl groups.

[0039] The phosphinic acid derivative (c4) in the present invention is different from the phosphorus-based compounds defined in the above (c1), (c2), and (c3), and is preferably represented by the following general formula (4). Specific examples thereof include HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), HCA-HQ (10-(2,5-dihydroxyphenyl)-10-hydro-9-oxa-10-phosphaphenanthrene-10-oxide), 10-(2,5-dihydroxynaphthyl)-10-hydro-9-oxa-10-phosphaphenanthrene-10-oxide, BCA (10-benzyl-10-hydro-9-oxa-10-phosphaphenanthrene-10-oxide), phenylphosphinic acid, diphenylphosphinic acid, and the like, all of which are available from Sanko Co., Ltd.

[0040] [ka]

[0041] (In the general formula (4), R represents a hydrogen atom, a phenoxy group, or an alkyl group having 1 to 10 carbon atoms.)

[0042] In the present invention, it is preferable that the halogen-free flame retardant (C) contains (c1). It is also preferable to use at least one selected from (c2), (c3), and (c4) in combination as the halogen-free flame retardant (C), and the mass mixing ratio of these is preferably (c1) / [phosphorus-based flame retardant other than (c1)]=(c1) / [(c2)+(c3)+(c4)]=30-70 / 70-30 in terms of bleeding and physical properties. However, when it is necessary to improve the retention stability, it is preferable that (c3) is used in a small amount, specifically, it is preferable that (c3) is 30 mass% or less in the halogen-free flame retardant (C), and it is more preferable that it is not used.

[0043] In the present invention, a non-halogen flame retardant other than the non-phosphorus flame retardant may be used. A phosphorus flame retardant and a non-phosphorus flame retardant may be used in combination. Examples of the non-halogen flame retardant other than the phosphorus flame retardant include a nitrogen flame retardant, a silicon flame retardant, a metal hydroxide, and a metal borate.

[0044] The amount of the halogen-free flame retardant (C) is 10 to 50 mass %, preferably 10 to 40 mass %, more preferably 12 to 30 mass %, and further preferably 15 to 25 mass %.

[0045] The glass fiber (D) in the present invention has an average fiber diameter of about 4 to 20 μm and a cut length of about 3 to 6 mm, and can be a very common one. The glass fiber is preferably pretreated with a coupling agent such as an organic silane compound, an organic titanium compound, an organic borane compound, or an epoxy compound. A polyester resin composition containing glass fiber treated with a coupling agent is preferable because it can provide molded products with excellent mechanical properties and appearance properties. In addition, when the coupling agent is not treated in other inorganic reinforcing materials, it can be added later.

[0046] The cross-sectional shape of the glass fiber may be a circular or non-circular glass fiber. The cross-sectional shape of the glass fiber is preferably a non-circular glass fiber in order to reduce warpage. The non-circular glass fiber may also have a substantially elliptical, substantially oval, or substantially cocoon-shaped cross section perpendicular to the fiber length, and the flatness is preferably 1.5 to 10, more preferably 1.5 to 8, and even more preferably 3 to 6. The flatness is the ratio of the major axis to the minor axis when a rectangle with the minimum area circumscribing the cross section perpendicular to the longitudinal direction of the glass fiber is assumed, and the length of the long side of this rectangle is the major axis and the length of the short side is the minor axis. The thickness of the glass fiber is not particularly limited, but the minor axis is about 1 to 20 μm and the major axis is about 2 to 100 μm.

[0047] The blending amount of the glass fiber (D) in the present invention is from 10 to 40% by mass, and preferably from 15 to 35% by mass.

[0048] The flame-retardant polyester resin composition of the present invention can contain a known inorganic filler in addition to the glass fiber (D). Examples of inorganic fillers include reinforcing fillers, conductive fillers, magnetic fillers, heat-conductive fillers, and fillers for suppressing thermal yellowing, depending on the purpose. Specific examples include glass beads, glass flakes, glass balloons, silica, talc, kaolin, mica, alumina, hydrotalcite, montmorillonite, graphite, carbon nanotubes, fullerene, indium oxide, tin oxide, iron oxide, magnesium oxide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, red phosphorus, calcium carbonate, lead zirconate titanate, barium titanate, aluminum nitride, boron nitride, zinc borate, barium sulfate, and non-acicular wollastonite, potassium titanate, aluminum borate, magnesium sulfate, zinc oxide, and calcium carbonate.

[0049] In addition to the above, the flame-retardant polyester resin composition of the present invention may contain, if necessary, within known ranges, light or heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, lubricants, crystal nucleating agents, release agents, antistatic agents, inorganic pigments, organic pigments, dyes, or other types of polymers.

[0050] The flame-retardant polyester resin composition of the present invention preferably contains the polybutylene phthalate resin (A), the polyethylene terephthalate resin (B1), the copolymer polyester resin (B2), the halogen-free flame retardant (C), and the glass fiber (D) in a total amount of 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more.

[0051] In the method for producing the flame-retardant polyester resin composition of the present invention, at least the above-mentioned components (A), (B1), (B2), (C), (D), etc. and other ingredients are blended in any order in the above-mentioned blend composition, and then mixed and melt-kneaded in a tumbler or Henschel mixer, etc. As the melt-kneading method, any method known to those skilled in the art can be used, and a single-screw extruder, twin-screw extruder, kneader, Banbury mixer, roll, etc. can be used, but it is preferable to use a twin-screw extruder.

[0052] In addition, glass fibers (D) that are easily damaged during extrusion are preferably fed from the side port of the twin-screw extruder to prevent damage to the glass fibers, but this is not particularly limited. In addition, the silane coupling agent may be added simultaneously with the raw material components other than (D), but it is preferable to add it to the (D) component in advance before adding it. In order to remove volatile components and decomposed low-molecular-weight components that are generated during processing, and to increase the reactivity of the modified resin and reinforcing material with the polyester resin, it is desirable to perform suction using a vacuum pump between the side opening for feeding the glass fibers and the die head at the tip of the extruder.

[0053] The flame-retardant polyester resin composition of the present invention has a melt mass flow rate (MFR) of 10 g / 10 min or more (measured at 265 ° C. and 2160 g load according to JIS K 7210-1:2014) at a moisture content of 0.05% (0.05% by mass) or less. If the MFR is lower than 10 g / 10 min, the resin composition will not reach the corners of the mold unless the cylinder temperature is increased or the injection pressure is increased during injection molding. On the other hand, if the injection temperature is increased or the injection pressure is increased, the retention performance of the resin composition will deteriorate and problems with the molded appearance such as silver will easily occur. The MFR is preferably 12 g / 10 min or more, more preferably 15 g / 10 min or more. The upper limit of the MFR is preferably 100 g / 10 min or less, more preferably 80 g / 10 min or less, and even more preferably 70 g / 10 min or less.

[0054] The flame-retardant polyester resin composition of the present invention has flame retardancy according to UL94 standard V-0 (1 / 16 inch thickness), and preferably UL94 standard V-0 (1 / 32 inch thickness).

[0055] The flame-retardant polyester resin composition of the present invention has a flexural strength of 140 MPa or more as measured in accordance with ISO-178, and satisfies the following formula (1). 0.5≦β / α (1) (Here, α is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265°C and a residence time of 5 minutes, and β is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265°C and a residence time of 10 minutes.) Here, the bending strength measured according to ISO-178 refers to the bending strength (α) of a molded product obtained by molding with a residence time of 5 minutes. The upper limit of the bending strength (α) is not particularly limited, but is about 220 MPa in the flame-retardant polyester resin composition of the present invention.

[0056] If β / α is less than 0.5, the retention stability of the polyester resin composition in the cylinder of the injection molding machine is poor, and the mechanical properties are significantly reduced at the beginning and end of molding. β / α is preferably 0.6 or more. The upper limit of β / α is 1.0. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0058] The characteristics and physical properties shown in the following examples and comparative examples were measured by the following test methods. (1) Reduced viscosity of polyester resin (dL / g): A 0.1 g sample was dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured at 30° C. using an Ubbelohde viscosity tube.

[0059] (2) Flexural strength: Measured in accordance with ISO-178. (3) Flexural modulus: Measured in accordance with ISO-178.

[0060] (4) Deflection temperature under load (HDT): A multipurpose test piece according to ISO-3167 was molded using an injection molding machine (Toshiba Machine Co., Ltd., IS80), and the HDT was measured at a load of 1.82 MPa in accordance with ISO-75.

[0061] (5)Melt mass flow rate (MFR): In accordance with JIS K-7210-1:2014, this is the amount of resin (g) that flows in 10 minutes at a temperature of 265°C with a load of 2160g. Each sample was loaded into the device in a dry state with a moisture content of 0.05% or less to prevent fluctuations in MFR due to moisture.

[0062] (6) Appearance of molded product: Using a 100mm x 100mm x 2mm thick textured plate mold, the resin was injection molded at a resin temperature of 265-280°C and a mold temperature of 80°C, 100°C or 120°C in an injection molding machine to obtain molded products with different mold temperatures. Among the obtained molded products, the one with the best appearance was visually evaluated as follows. ◯: There is no glass fiber floating over the entire surface of the plate, and the surface gloss is excellent. △: Glass fiber floating is observed on the end face away from the gate. ×: Glass fibers are seen floating over the entire surface of the molded product, and the surface gloss is poor.

[0063] (7) Warpage: Using a film gate mold with a size of 100 mm x 100 mm x 2 mm thickness and a rib on one side, a molded product with five ribs, each 100 mm long, 1 mm high, and 1 mm thick, was molded perpendicular to the resin flow direction under the same molding conditions as the molded product in section (6) (mold temperatures: 80°C, 100°C, 120°C), and the amount of warpage was measured (the value of A in Figure 1 was calculated as the average value of three molded products with different mold temperatures). ×: Warpage deformation > 3mm △: 3mm ≧ Warpage ≧ 2mm ○: Warpage deformation amount <2mm

[0064] (8) Retention stability (β / α): ISO dumbbell pieces were continuously injection molded using an injection molding machine (IS80, manufactured by Toshiba Machine Co., Ltd.) at a cylinder temperature of 260°C, a mold temperature of 80°C, and a cycle time of 60 seconds, and the bending strength was measured from the ISO dumbbell pieces from the 5th and 10th shots to calculate β / α. The dumbbell piece from the 5th shot was used to measure the bending strength (α) of a molded product obtained by molding with a residence time of 5 minutes, and the dumbbell piece from the 10th shot was used to measure the bending strength (β) of a molded product obtained by molding with a residence time of 10 minutes. The bending strength in (2) refers to α.

[0065] (9) Flammability test: Flammability was evaluated in accordance with UL94 on test specimens of thickness 1 / 16 inch and 1 / 32 inch.

[0066] The raw materials used in the examples and comparative examples are as follows: Polybutylene terephthalate resin (A): Toyobo, reduced viscosity 0.83 dL / g Polyethylene terephthalate resin (B1): Toyobo, RE-530 (reduced viscosity 0.63 dL / g)

[0067] Copolymer polyester resin (B2-1): Copolymer with a composition ratio of TPA / EG / NPG = 100 / 70 / 30 mol%, reduced viscosity 0.83 dL / g Copolymer polyester resin (B2-2): Copolymer with a composition ratio of TPA / IPA / EG / NPG = 50 / 50 / 50 / 50 mol%, reduced viscosity 0.56 dL / g Copolymer polyester resin (B2-3): Copolymer with a composition ratio of TPA / EG / 1,2PG = 100 / 30 / 70 mol%, reduced viscosity 0.56 dL / g

[0068] Halogen-free flame retardant (C-1): Aluminum phosphinate (Clariant Japan, EXOLIT OP1240) Halogen-free flame retardant (C-2): Aluminum phosphinate / Hexaphenoxytriphosphazene / Melamine polyphosphate = 42 / 37 / 21 (mass ratio)

[0069] Glass fiber (D): Nippon Electric Glass Co., Ltd., T-120H

[0070] The following substances were used as other additives: Antioxidant: Irganox 1010 (Ciba Specialty Chemicals) Release agent: WE40 (Clariant Japan) Black pigment: ABF-T9534 (manufactured by Resino Color Industries)

[0071] [Copolymer polyester resin (B2-1): Polymerization example of TPA / EG / NPG copolymer] 2,414 parts by mass of terephthalic acid (TPA), 1,497 parts by mass of ethylene glycol (EG), and 515 parts by mass of neopentyl glycol (NPG) were charged into an esterification reaction tank having a volume of 10 L equipped with a stirrer and a distillation condenser, and as a catalyst, germanium dioxide was added as an 8 g / L aqueous solution so as to contain 30 ppm of germanium atoms relative to the produced polyester, and cobalt acetate tetrahydrate was added as a 50 g / L ethylene glycol solution so as to contain 35 ppm of cobalt atoms relative to the produced polymer. The temperature in the reaction system was then gradually raised to 240°C, and the esterification reaction was carried out for 180 minutes at a pressure of 0.25 MPa. After it was confirmed that no more water was distilled from the reaction system, the pressure in the reaction system was returned to normal, and trimethyl phosphate was added as a 130 g / L ethylene glycol solution so that the produced polymer contained 52 ppm of phosphorus atoms. The obtained oligomer was transferred to a polycondensation reaction tank, and the temperature was gradually increased while the pressure was reduced until the temperature reached 280°C and the pressure reached 0.2 hPa. The reaction was continued until the torque value of the stirring blade corresponding to the intrinsic viscosity reached the desired value, and the polycondensation reaction was terminated. The reaction time was 100 minutes. The obtained molten polyester resin was extracted in the form of strands from the extraction port at the bottom of the polymerization tank, cooled in a water tank, and then cut into chips. As a result of NMR analysis of the copolymerized polyester obtained as described above, the dicarboxylic acid component was found to have a composition of 100 mol % of terephthalic acid, and the diol component was found to have a composition of 70 mol % of ethylene glycol and 30 mol % of neopentyl glycol.

[0072] The copolymer polyester resins (B2) described in the other examples were polymerized in the same manner as the TPA / EG / NPG copolymer (B2-1), except for the raw materials and composition ratios used.

[0073] Examples 1 to 6, Comparative Examples 1 to 5 The flame-retardant polyester resin compositions of the Examples and Comparative Examples were produced by weighing the above raw materials according to the blending ratios (mass%) shown in Table 1 and melt-kneading them in a 35φ twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.) at a cylinder temperature of 270°C and a screw rotation speed of 100 rpm. Raw materials other than glass fiber were fed into the twin-screw extruder from a hopper, and glass fiber was fed by side feeding from a vent port. The resulting pellets of the flame-retardant polyester resin composition were molded into evaluation samples using an injection molding machine. The evaluation results are shown in Table 1.

[0074] [Table 1]

[0075] From Table 1, it can be seen that the flame-retardant polyester resin compositions described in Examples 1 to 6 obtained good results in all items, and all of the strength, rigidity, heat deformation, moldability, appearance, low warpage, flame retardancy, and retention stability were well balanced. On the other hand, Comparative Example 1 was poor in warpage because it did not contain the copolymer polyester resin (B2), and Comparative Example 2 was poor in heat deformation (deflection temperature under load) because it did not contain the polyethylene terephthalate resin (B1). In addition, Comparative Examples 3 and 4, which had MFR lower than the specified value, had low fluidity, and it was not possible to obtain the desired molded product in terms of appearance and warpage, and Comparative Example 5 had poor retention stability due to the flame retardant. [Industrial Applicability]

[0076] The flame-retardant polyester resin composition of the present invention has high strength and high rigidity, yet suffers from little warpage, resulting in good molded product appearance, and further has excellent retention stability, making it applicable to a wide range of applications such as electrical and electronic parts, machine mechanism parts, and automotive parts. [Explanation of symbols]

[0077] L: Flow direction of the resin composition W: perpendicular to the flow of the resin composition 1: Molded product 2: Film Gate 3: Rib A: Warpage deformation amount

Claims

1. A flame-retardant polyester resin composition comprising: 3 to 74 mass% of a polybutylene phthalate resin (A), 3 to 60 mass% of a polyethylene terephthalate resin (B1), 3 to 50 mass% of a copolymer polyester resin (B2), 10 to 50 mass% of a halogen-free flame retardant (C), and 10 to 40 mass% of a glass fiber (D), The copolymerized polyester resin (B2) is a polyester resin in which ethylene terephthalate units are copolymerized with at least one member selected from the group consisting of neopentyl glycol, 1,2-propanediol, diethylene glycol, 1,4-cyclohexanedimethanol, and isophthalic acid, The halogen-free flame retardant (C) is a metal phosphinate, The flame-retardant polyester resin composition has a melt mass-flow rate (MFR) of 10 g / 10 min or more and 100 g / 10 min or less at a moisture content of 0.05% or less (measured at 265° C. and a load of 2160 g in accordance with JIS K 7210-1:2014); The flame-retardant polyester resin composition exhibits flame retardancy of UL94 standard V-0 (1 / 16 inch thickness), The flame-retardant polyester resin composition has a flexural strength of 140 MPa or more as measured in accordance with ISO-178, and satisfies the following formula (1): 0.5≦β/α・・・(1) (Here, α is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265° C. and a residence time of 5 minutes, and β is the bending strength of a molded article obtained by molding a flame-retardant polyester resin composition at a cylinder temperature of 265° C. and a residence time of 10 minutes.)

2. A molded article which is an electrical / electronic part, an office automation device, a home appliance part, an automobile part or a mechanical mechanism part, comprising the flame-retardant polyester resin composition according to claim 1.

Citation Information

Patent Citations

  • Structure and manufacture of crystal vibrator

    JP1978096690A

  • Flame-retardant resin composition

    JP1993070671A

  • Flame-retardant polybutylene terephthalate composition and method for making polybutylene terephthalate composition flame-retardant

    JP1999152402A

  • Flame-retardant resin composition and molding product comprising the same

    JP2000103973A

  • Flame retardant combination

    JP2001072978A